Pengaruh Nilai Pelanggan dan Pengalaman Pengunjung Terhadap Loyalitas Pengunjung di Jakabaring Sport City - Gusma, Esxi Martia; Nurmalinda, Elda (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Institut Pariwisata Trisakti, 2024)
The sports and recreation sector in Jakabaring Sport City, Palembang, plays an important role in improving the quality of life of the community, but the challenge of maintaining visitor loyalty is a major concern. This research aims to analyze the influence of customer value and visitor experience on loyalty at Jakabaring Sport City. The research method used was quantitative with multiple regression analysis, involving 135 respondents selected by accidental sampling. Data was collected through a questionnaire with a Likert Scale. The results of the analysis show that customer value and visitor experience partially have a significant effect on loyalty. The conclusion of this research is that increasing the value and experience felt by visitors can encourage higher loyalty. The advice for managers is to continue to improve the quality of services and facilities, as well as create interesting experiences. The Palembang City Government is advised to support the development of infrastructure that supports accessibility, while visitors are expected to provide feedback for continuous improvement. This research provides an important contribution for managers in designing effective strategies to attract and retain visitors to Jakabaring Sport City. Keywords: customer value, visitor experience, customer loyalty, satisfaction